Implementation and validation of a 24/7 system for the monitoring of antiepileptic drugs - Khromov, Tatjana; Dihazi, Gry Helene; Brockmeyer, Phillipp; Fischer, Andreas; Streit, Frank (Frontiers in Neurology, 2025)
BackgroundEpilepsy is a common neurological disorder associated with seizures that impact patients' quality of life. Treatment includes antiepileptic drugs (AEDs), each effective only at a specific dose, making continuous therapeutic drug monitoring (TDM) useful in clinical cases under inpatient conditions. Conventional liquid chromatography-tandem mass spectrometry (LC-MS/MS) lacks automation for 24/7 operation, limiting clinical applicability. This study validates a fully automated 24/7 AED monitoring system using the Clinical Laboratory Automated Sample Preparation Module 2030 (CLAM-2030).MethodsThe method was validated according to U.S. Food and Drug Administration (FDA) and European Medicines Agency (EMA) guidelines by evaluating linearity, precision, accuracy, carry over, matrix effects, and calibration stability. Twenty-six AEDs were quantified in plasma using multiple reaction monitoring (MRM) transitions in positive and negative electrospray ionization modes. Sample preparation was fully automated: 20 μL methanol was used to wet the column, followed by 20 μL internal standard and 100 μL acetonitrile for protein precipitation. The supernatant was filtered and injected directly into the LC system. Chromatographic separation was achieved within 4.5 min using a C18 column (2.1 × 50 mm, 2.7 μm) under gradient conditions with a mobile phase of 0.2 mM ammonium formate and 0.002% formic acid.ResultsThe method demonstrated excellent linearity over the validated concentration ranges (R2 > 0.99 for all analytes). Within-run imprecision was <15% at the lower limit of quantitation (LLOQ), while between-run imprecision was <10% for most AEDs. Accuracy was within ±10% of nominal concentrations at all quality control (QC) levels. Matrix effects were within acceptable limits (<30% variation) for 23 of 26 analytes, with compensatory corrections applied for carbamazepine-D10, felbamate-D4, and levetiracetam-D6. Carry over was negligible [<2% for all AEDs except retigabine and N-desmethylselegiline (NDMS), which remained below 6.5%]. Calibration stability was maintained over 5 days with concentration and peak area variation <10%. An interlaboratory comparison (ring test) showed a relative standard deviation <20% for all analytes.ConclusionThis study establishes a robust, fully automated, high-throughput method for continuous AED monitoring in the clinical setting. The CLAM-2030-LCMS-8060NX system enables reliable 24/7 TDM with minimal technical expertise, ensuring optimized AED therapy and improved patient outcomes.